2021
DOI: 10.1186/s12905-021-01430-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of osteoporosis knowledge and beliefs with preventive behaviors in postmenopausal breast cancer survivors

Abstract: Background Postmenopausal breast cancer survivors (PBCS) are at increased risk of bone loss and fractures due to age-related decline of estrogen, and this risk is compounded by aromatase inhibitor cancer therapy. Several patient-level targetable risk factors can mitigate osteoporosis risk; however, adequate health behavior and risk perception in this population are underreported. The goal of this study was to evaluate osteoporosis knowledge and beliefs and assess their association with engageme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Osteoporosis is an increasingly prominent problem worldwide and causes a significant disease burden due to its high morbidity, disability, and mortality (Shen et al, 2022). Elevating knowledge and creating awareness of osteoporosis can effectively prevent and treat the condition by increasing the likelihood of early detection (Bailey & Lin, 2021). It is thus essential to assess the knowledge level related to osteoporosis prevention among high‐risk populations to guide effective and targeted intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is an increasingly prominent problem worldwide and causes a significant disease burden due to its high morbidity, disability, and mortality (Shen et al, 2022). Elevating knowledge and creating awareness of osteoporosis can effectively prevent and treat the condition by increasing the likelihood of early detection (Bailey & Lin, 2021). It is thus essential to assess the knowledge level related to osteoporosis prevention among high‐risk populations to guide effective and targeted intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…A study among postmenopausal breast cancer survivors showed low mean score concerning osteoporosis knowledge. Only 47% reported commitment in strength-training exercise [ 47 ]. Another study evaluating osteoporosis knowledge in women with premature ovarian insufficiency and early menopause showed that there are knowledge gaps regarding risk factors and treatment options [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, researchers found that the great majority (80%) of women being treated with AIs for postmenopausal breast cancer wanted to be proactive to prevent bone loss but that they had little knowledge about osteoporosis. 29 The women in the study knew the importance of calcium and vitamin D supplementation, but most did not know the importance of weight-bearing exercise and strength training. 29 Thus, initial interventions include education with a focus on reducing modifiable risk factors.…”
Section: Interventions To Reduce Bone Fracture Riskmentioning
confidence: 99%
“…29 The women in the study knew the importance of calcium and vitamin D supplementation, but most did not know the importance of weight-bearing exercise and strength training. 29 Thus, initial interventions include education with a focus on reducing modifiable risk factors. Lifestyle changes that promote bone health include cessation of cigarette smoking and reduction or cessation of alcohol consumption, increasing physical activity including weight-bearing activities, and minimizing the risk of falling.…”
Section: Interventions To Reduce Bone Fracture Riskmentioning
confidence: 99%